Older Workers and Labour Market Exclusion Processes A Life Course perspective - Burnay, Nathalie; Ogg, Jim.; Krekula, Clary; Vendramin, Patricia; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2023)
This open access book addresses the important and neglected question of older workers who are excluded from the labour market. It challenges post-capitalist discourses of active ageing with a focus on restrictive end-of-career and retirement measures. The book demonstrates how a paradigm shift is generating real processes of exclusion for important sectors of the population. By providing strong empirical evidence from different contexts, the impact of different life course trajectories on the risks and the opportunities at the end of career are demonstrated. The organisation of workplace and institutional frameworks which reinforce inequalities are also presented. As such the book is an essential reading for students, academics and policy makers who seek to understand how exclusion processes operate to the disadvantage of older workers in the labour market. .
Chapter 1. Introduction. Chapter 2. Gender, Transitions and Turning Points: The Life Course and Older Workers$1 (BTrajectories in Different US Occupations -- Chapter 3. The Loss of Work Motivation Among Older Male Employees: Critical Perspectives to Policies Aimed at Extending Working Life in Finland -- Chapter 4. Transitions into Precarity at Work Among Older Men in the Metal Industry in Portugal and Sweden -- Chapter 5. Older Workers and Their Relations to the Labour Market in Albania -- Chapter 6. Attitudes Towards Older People in the Labour Market and in Politics: A Cross-National Comparison -- Chapter 7. Sustainable Work in an Ageing Perspective, Gender and Working Life Course -- Chapter 8. Working Conditions and Retirement Preferences: The Role of Health and Subjective Age as Mediating Variables in the Association of Poor Job Quality with Early Retirement -- Chapter 9. Health, Working Conditions and Retirement -- Chapter 10. From Early Retirement to Extending Working Life: Institutionalisation and Standardization at the End of Career in Belgium -- Chapter 11. Social Exclusion in Later Life, Evidence from the European Social Survey.s
Keywords: Life cycle, Human; Labor economics; Population -- Economic aspects; Aging; Social structure; Equality; Industrial sociology; Life Course; Labor and Population Economics; Ageing; Social Structure; Sociology of Work